Membangun Fondasi Complementary Agenda Untuk Transformasi Digital Bisnis (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
Digital innovation is fundamentally changing the business landscape, driving advances in products, processes and business models. It involves complex interactions between technological and social aspects, creating ambiguity between process and product. It is important to understand how digital innovation impacts business process management. This study uses a literature approach to explore the concepts of digital innovation and business process management. The research was conducted by analyzing related literature from various academic and professional sources, including scientific journals, books and industry publications. Digital innovation not only creates technological progress, but also changes social processes and organizational structures. This phenomenon can be seen in platforms such as Uber or DevOps, which show a close connection between product and process. Digital innovation also enables continuous evolution and improvement of products and processes over time. Business process management is becoming increasingly important in facing the challenges and opportunities brought by digital innovation. Agile and adaptive process management strategies are needed to cope with rapid changes in the digital business environment. From the literature analysis, it appears that integration between digital innovation and business process management is very important. To optimize the benefits of digital innovation, organizations need to adopt an agile and adaptive approach in their process management. This involves continuous adaptation to technological and social changes as well as increased collaboration between various functions within the organization. Suggestions for future research are to conduct more in-depth empirical studies to understand the concrete impact of digital innovation on business process management, as well as to develop a practical framework for applying process management principles in the context of digital innovation.